Well-defined star polymers for co-delivery of plasmid DNA and imiquimod to dendritic cells. (15th January 2017) - Lin, Wenjing; Hanson, Samuel; Han, Wenqing; Zhang, Xiaofang; Yao, Na; Li, Hongru; Zhang, Lijuan; Wang, Chun
Graphical abstract: Abstract: Co-delivery of antigen-encoding plasmid DNA (pDNA) and immune-modulatory molecules has importance in advancing gene-based immunotherapy and vaccines. Here novel star polymer nanocarriers were synthesized for co-delivery of pDNA and imiquimod (IMQ), a poorly soluble small-molecule adjuvant, to dendritic cells. Computational modeling and experimental results revealed that the polymers formed either multimolecular or unimolecular core-shell-type micelles in water, depending on the nature of the outer hydrophilic shell. Micelles loaded with both IMQ and pDNA were able to release IMQ in response to intracellular pH of the endo-lysosome and transfect mouse dendritic cells (DC2.4 line) in vitro . Importantly, IMQ-loaded micelle/pDNA complexes displayed much enhanced transfection efficiency than IMQ-free complexes. These results demonstrate the feasibility of co-delivery of pDNA and IMQ to antigen-presenting cells by multifunctional polymer nanocarriers with potential use in gene-based vaccine approaches.